Case Report: Further Delineation of Neurological Symptoms in Young Children Caused by Compound Heterozygous Mutation in the PIEZO2 Gene - Klaniewska, Magdalena; Jedrzejowska, Maria; Rydzanicz, Malgorzata; Paprocka, Justyna; Biela, Mateusz; Wolanska, Ewelina; Pollak, Agnieszka; Debek, Emilia; Sasiadek, Maria; Ploski, Rafal; Gos, Monika; Smigiel, Robert (Frontiers in Genetics, 2021)
PIEZO2 protein is a unique ion channel that converts mechanical impulses into cellular signals in somatosensory neurons and is involved in various mechanotransduction pathways. The recessive PIEZO2 loss-of-function pathogenic variants are associated with distal arthrogryposis with impaired proprioception and touch (DAIPT). Here we present three new DAIPT patients. The genetic diagnosis was established by exome sequencing and let us to identify 6 novel loss-of-function PIEZO2 variants: four splicing (c.1080+1G>A, c.4092+1G>T, c.6355+1G>T, and c.7613+1G>A), one nonsense (c.6088C>T) and one frameshift variant (c.6175_6191del) for which mosaic variant was identified in proband's mother. All patients presented typical symptoms at birth, with congenital contractures, bilateral hip dislocation/dysplasia, generalized hypotonia, transient feeding and difficulties. Two were afflicted by transient respiratory insufficiency. In all children motor development was severely delayed. In one patient, severe cognitive delay was also observed. Moreover, among the cases described by us there is the youngest diagnosed child to date.